Different Sector Calculations in Direct Torque Control of Permanent Magnet Synchronous Motors and Their Effect on Control - Bozkurt, Ebubekir; Polat, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2024)
Permanent magnet synchronous motors (PMSM) are widely preferred for their high energy efficiency, maximum torque at zero speed, and high power per unit weight. They are widely used in space technologies, electric cars, bicycles, and the medical world. Direct torque control and its derivatives are effectively used in the control of these motors from vector control methods. Errors in the parameter calculations in direct torque control directly affect system stability. Ensuring the control stability of the system is an important issue for safe use of these motors. The correct calculation of sector and sector angle in PMSM is one of the basic factors in selecting appropriate driver switching. In this study, sector calculations were made using different sector angles in the switching table direct torque control of PMSM. The sector angles used in sector calculations were performed using the alpha-beta axis, rotor angle, and load angle. Both sector calculations were successful in terms of control. However, in the sector calculation performed over the rotor angle and load angle, since the load angle is available in the switching table direct torque control's load angle dependent torque calculation technique, an additional angle calculation for the sector is not needed. This situation shows that sector calculation based on rotor angle and load angle can be preferred due to the torque calculation method. © 2024 IEEE.
2024 International Conference on Sustainable Power and Energy, ICSPE 2024 -- 28 November 2024 through 29 November 2024 -- Raigarh -- 207741
Keywords: control; DTC; load angle; PMSM; sector